Evaluation of digitalis in cardiac failure. Issue 6328 (22nd May 1982) - Murray, R G; Tweddel, A C; Martin, W; Pearson, D; Hutton, I; Lawrie, T D
Abstract : Ten patients in sinus rhythm with symptomatic cardiac failure participated in a study investigating the value of digitalis at rest and during dynamic exercise. A haemodynamic profile and left ventricular ejection fraction were measured before treatment, after intravenous ouabain, and after six weeks of maintenance treatment with digoxin. There was no significant change in the haemodynamic profile or in the left ventricular ejection fraction at rest after either glycoside. During exercise there was a significant reduction in left ventricular filling pressure from 39 +/- 3 mm Hg to 34 +/- 3 mm Hg (p less than 0.05) after ouabain and to 33 +/- 3 mm Hg (p less than 0.02) after digoxin. Cardiac index improved from 33 +/- 0.3 1/min/m2 to 4.0 +/- 0.4 l/min/m2 (p less than 0.01) after ouabain and to 3.8 +/- 0.4 l/min/m2 (p less than 0.01) after digoxin. During exercise stroke volume index and stroke work index also improved significantly with both glycosides. This was accompanied by an increase in left ventricular ejection fraction from 29 +/- 2% to 36 +/- 3% (p less than 0.05) after ouabain and digoxin. In this study both intravenous ouabain and maintenance treatment with oral digoxin exerted a modest positive inotropic effect in patients with cardiac failure in sinus rhythm. The haemodynamic benefit, however, was manifest only during exertion.